Diskriminasi Perempuan pada Film â€œPengabdi Setanâ€ dalam Perspektif CEDAW - Maria Indira Aryani; Endiva Khoirum Putri (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This paper aims to analyse the implementation of gender stereotype in the society as a tool to generalise booth men and women ideal role in a family. The gaps between the portrayal of men and women, along with societyâ€™s expectations are putting women into more vulnerable position towards gender discrimination. Not only in a reality, this idea manifestation also reflected into horor movie industry. One of it was in the film titled â€œPengabdi Setanâ€ by Joko Anwar. Plenty of moral assertion of women in the society are shown in several scenes. Womenâ€™s portrayal as a monster or even Satan if they arenâ€™t able to follow the ideal expectations of womenâ€™s role, that are to be a wife, gave birth and became a mom. This indicate that the gender discrimination towards women is real, even in several countries that already ratify the CEDAW (The Convention on the Elimination of All Forms of Discrimination against Women) which is a international convention focusing on eliminating all forms discriminations against women in all field â€“ including movie. The identifications of discrimination forms in the movie â€œPengabdi Setanâ€ by Joko Anwar will also be analyse using content analyses method using CEDAW perspective. Keywords : Women Discrimination; Gender Stereotype; CEDAW; Horor Movie